Oncogenic human papillomaviruses and ploidy in cervical lesions. - Rihet, S (1996)
AIM: To compare ploidy measurements obtained on tissue sections of selected low and high grade squamous intraepithelial lesions containing oncogenic HPV (types 16, 18 or 33) detected by in situ hybridisation (ISH) or PCR. METHODS: DNA ploidy was assessed by image cytometry after Feulgen staining of contiguous serial sections of eight lesions exhibiting atypical squamous cells or squamous atypia and 53 low and 63 high grade squamous intraepithelial lesions in which HPV had been detected by ISH or PCR. RESULTS: Aneuploidy was strongly associated with the presence of oncogenic HPV, being detected in 50% of lesions with squamous atypia and 75.5% of the low and 95.2% of the high grade squamous intraepithelial lesions. The multiploid profile was highly associated with high grade lesions and with the pattern of HPV DNA integration. CONCLUSIONS: The presence of aneuploidy is strongly suggestive of the presence of oncogenic HPV types. Combining the detection of HPV by ISH and PCR with DNA image cytometry may provide the pathologist and the physician with important prognostic information about low grade lesions, especially when these lesions have a multiploid DNA profile and contain oncogenic HPV.